Shell Shape Variations and Sexual Dimorphism of Pomacea canaliculata using Geometric Morphometric Analysis - Generol, Yashica; P. Magdugo, Rexie; Jhun Almadin , Florence (Jurusan Biologi Universitas Negeri Makassar, 2025)
Pomacea canaliculata or Golden Apple Snail (GAS) existed to be a rice pest in the Philippines and Asia. Likewise, geographic location also contributes to its increasing populations, thus making it invasive among freshwater habitats and rice field areas. This study was conducted to describe shell shape variations and sexual dimorphism among the populations of P. canaliculata. A total of 120 samples were randomly collected in the downhill and uphill geographic locations in Mambajao, Camiguin Island, Mindanao, Philippines. To determine the variations and sexual dimorphism in the shell shape of golden apple snail, coordinates were administered to relative warp analysis and the resulting data were subjected to Multivariate Analysis of Variance (MANOVA), Principal Component Analysis (PCA) and Canonical Variate Analysis (CVA). The results show statistically significant (P < 0.01). While male and female spire height, body size, and shell shape opening also show significant variations. These phenotypic distinctions could be associated with geographic isolation, predation, and a nutrient component of the gastropods. Thus, the importance of using geometric morphometric advances in describing sexual dimorphism in the shell shape of P. canaliculata.